Non Thermal Plasma Sources of Production of Active Species for Biomedical Uses: Analyses, Optimization and Prospect - Yousfi, M.; Merbahi, N.; Sarrette, J. P.; Eichwald, O.; Ricard, A.; Gardou, J.P.; Ducasse, O.; Benhenni, M. (IntechOpen, 2011)
None